ANALISIS INDEKS VEGETASI MENGGUNAKAN CITRA ALOS/AVNIR-2 DAN SISTEM INFORMASI GEOGRAFI (SIG) UNTUK EVALUASI TATA RUANG KOTA DENPASAR - As-syakur, A. Rahman; Adnyana, I.W. Sandi (Bumi Lestari; Vol 9 No 1 (2009), 2009)
High population density is the main factor in environmental problems, where the high speed of human growth caused the vegetation area became deminishing. The aims of this research was to functionized the ALOS/AVNIR-2 image satellites and GIS to calculate the percentage of vegetation in Denpasar city with three index vegetation formulas: NDVI, SAVI dan MSAVI in order to get one formula to build the distribution map based on the percentage of vegetation. This map was used to evaluate the urban planning map 2003 in Denpasar city. Result showed that there was relationships between vegetation index of ALOS/AVNIR-2 images and percentage of vegetations, where the vegetation index of NDVI and SAVI had the highest coefficient determination. The formula of “Percentage Vegetation = 132.71 (NDVI)2 + 3.461 (NDVI) + 5.6775” was used to generate the percentage distribution vegetation map. Based on that map, the dominant vegetation distribution found in settlement area (with percentage vegetation area) lower than 25%. The urban planning for green open area “KDB” 0% was dominated by the area which had a percentage of vegetation between 25-50% and 50-75%. In the other hand, the urban planning for “Tahura”, was dominated by the area which had a percentage of vegetation of more than 75%.
Keywords: vegetation index, percentage vegetation, urban planning, ALOS/AVNIR-2